An evaluation of the 'protect their future' video intervention on parents' intentions to immunize adolescents. (2nd October 2018) - Cohen, Elisia L.; Head, Katharine J.; Westgate, Philip; Vanderpool, Robin C.; Parrish, Adam; Reno, Jenna; Bachman, Audrey; Vos, Sarah; Wombacher, Kevin
ABSTRACT: Background: This study tested the influence of the 'Protect Their Future' video intervention on adult intentions to vaccinate their adolescents. Method: The study included 529 parents of 11- to 19-year-old adolescents in Appalachian Kentucky enrolled in group randomized controlled trial arms at 14 health clinic and community sites (seven in each arm) across eight counties. Approximately half the parents ( n = 263) were enrolled in the full intervention. Participants in the intervention and control did not significantly differ by education, race, percentage working full-time or gender. Results: Individuals in the intervention were 3.2 times more likely (P = .005) to intend for their female adolescent to receive HPV immunization. However, there was no support for the multivariate model for male HPV immunization. Inconsistent reasoned action findings for HPV, meningitis and flu intentions are also discussed. Conclusions: This study suggests the importance of immunization-specific information motivating parents embedded in a general 'adolescent vaccination platform' promotion video may be most supportive in immunization contexts where the descriptive norms are well established parents, as is currently the case for meningitis, flu and female HPV immunization rates. Implications for male HPV parental education needs are discussed.